Does REACH provide sufficient information to regulate mutagenic and carcinogenic substances?. Issue 8 (17th November 2019) - Woutersen, Marjolijn; Beekman, Martijn; Pronk, Marja E. J.; Muller, Andre; de Knecht, Joop A.; Hakkert, Betty C.
Abstract: The REACH (Registration, Evaluation, Authorisation and Restriction of Chemicals) data requirements for mutagenicity and carcinogenicity have been compared to the criteria for classification under Classification, Labelling and Packaging (CLP) and the studies used as key evidence by Committee for Risk Assessment (RAC) in drafting its opinions on the appropriate classification. This comparison revealed that the REACH information requirements will not provide sufficient information to conclude a substance is a Cat 1B mutagen and/or carcinogen. In addition, requiring such information via a substance evaluation under REACH requires a large investment from the Member States and takes years. Classification and labeling is essential in the communication of the hazardous properties of substances and mixtures and is amongst others an important first step in the identification of a substance as a Substance of Very High Concern (SVHC). REACH will hardly generate sufficient information for classification of substances as category 1B for mutagenicity and carcinogenicity. Therefore, indications of very severe hazards of substances are missed and health risks could occur. There are various ways to deal with this problem, however as most of these require adaptation of regulations this will cost considerable time and political will. This study is a first step to raise awareness for the problem and to start a discussion to search for a sustainable solution.